Research on Optimization Design of Prefabricated ECC/RC Composite Coupled Shear Walls Based on Seismic Energy Dissipation - Jian Yang; Ming Sun; Guohuang Yao; Haizhu Guo; Rumian Zhong (Buildings, 2024)
This study explores an advanced prefabricated composite structure, namely ECC/RC composite shear walls with enhanced seismic performance. This performance enhancement is attributed to the strategic use of engineered cementitious composites (ECC) known for their superior ductility. The study conducts both experimental and numerical simulation analyses to scrutinize the seismic energy absorption capabilities of this innovative structure. Emphasis is placed on critical aspects, such as the optimal deployment areas for ECC within composite coupling beams and shear walls, the grade of ECC strength, the proportion of stirrups in coupling beams, and the caliber of longitudinal reinforcement. Through finite element analysis, this research quantitatively assesses the impact of these variables on seismic energy dissipation, incorporating evaluations of load–displacement hysteretic behaviors and the energy dissipation potential of ECC/RC shear wall samples. The findings suggest the optimal ECC application in the coupling beams, and within a 14% structural height at the base of shear walls. Recommended design parameters include an ECC strength grade of E40 (40 MPa), longitudinal reinforcement of HRB400 (400 MPa), and a stirrup ratio in coupling beams of 0.5%.